Multilayer polyimide film, metal foil-clad laminate, and method for producing multilayer polyimide film
The multi-layer polyimide film is formed through the coextrusion-casting coating method and imidizing process, which solves the problems of low productivity and high dielectric loss tangent in the prior art, and achieves low high frequency region Loss and excellent bonding characteristics.
Patent Information
- Application Number
- CN202180070660.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-01
- Filing Date
- 2021-10-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-10-11
AI Technical Summary
The prior art is difficult to improve the productivity of the multi-layer polyimide film on the basis of ensuring the adhesive properties to the metal layer and reducing the dielectric loss tangent.
The non-thermoplastic polyimide layer and the adhesive layer are formed by coextrusion-casting coating, and heated under the highest temperature of 360°C or above through the imidization process to imide the polyamic acid. to form a multi-layer polyimide film.
It is achieved to reduce the dielectric loss tangent in high-frequency regions (such as above 10 GHz), while ensuring excellent bonding characteristics to the metal layer and improving productivity.
Smart Images

Figure CN116507667B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a multilayer polyimide film, a metal foil-clad laminate and a method for producing the multilayer polyimide film. Background Art
[0002] In recent years, with the growing demand for electronic products, primarily smartphones, tablets, and laptop computers, the demand for flexible printed circuits (hereinafter sometimes referred to as "FPCs") has been growing. FPCs made from multilayer polyimide films containing a thermoplastic polyimide layer as an adhesive layer offer excellent heat resistance and flexibility, and therefore are expected to see further growth in demand.
[0003] Furthermore, with the recent increase in high-speed signal transmission in electronic devices, the demand for electronic substrate materials with lower dielectric constants and dielectric loss tangents is increasing to achieve the higher frequencies of electrical signals propagating through circuits. Lowering the dielectric constant and dielectric loss tangent of electronic substrate materials is effective in suppressing transmission losses of electrical signals. In recent years, at the dawn of the IoT society, the trend toward higher frequencies has been advancing, leading to a demand for substrate materials that can suppress transmission losses in the 10 GHz and above range, for example.
[0004] Polyimide films exhibiting a low dielectric loss tangent are known as films used in circuit boards capable of adapting to high frequencies. For example, Patent Document 1 discloses a multilayer polyimide film having a non-thermoplastic polyimide layer exhibiting a low dielectric loss tangent. Furthermore, Patent Document 2 discloses a multilayer polyimide film having a thermoplastic polyimide layer on at least one side of a non-thermoplastic polyimide layer, wherein the dielectric loss tangent at 10 GHz is 0.004 or less.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2018-145303
[0008] Patent Document 2: International Publication No. 2018 / 061727 Summary of the Invention
[0009] Problems to be solved by the invention
[0010] However, it is difficult to obtain a multilayer polyimide film with excellent productivity while ensuring adhesion properties to the metal layer (specifically, adhesion to the metal layer, embedding properties in the metal layer, etc.) and reducing the dielectric loss tangent using only the technologies described in Patent Documents 1 and 2.
[0011] The present invention has been completed in view of these problems, and its purpose is to provide a multilayer polyimide film and its production method that are excellent in productivity while ensuring adhesion properties with a metal layer and reducing the dielectric loss tangent; and a metal foil-clad laminate obtained by using the multilayer polyimide film.
[0012] Solutions for solving problems
[0013] The multilayer polyimide film of the present invention comprises a non-thermoplastic polyimide layer and an adhesive layer disposed on at least one side of the non-thermoplastic polyimide layer, wherein the adhesive layer comprises polyimide. The dielectric loss tangent of the non-thermoplastic polyimide layer at a frequency of 10 GHz, a temperature of 23° C., and a relative humidity of 50% is 0.0030 or less. The adhesive layer does not have a melting peak or the heat of melting of the melting peak is 1.0 J / g or less within a temperature range of 100° C. to 420° C. The polyimide contained in the adhesive layer comprises one or more tetracarboxylic dianhydride residues selected from the group consisting of pyromellitic dianhydride residues and 3,3',4,4'-biphenyltetracarboxylic dianhydride residues, and one or more diamine residues selected from the group consisting of 1,3-bis(4-aminophenoxy)benzene residues and 4,4'-diamino-2,2'-dimethylbiphenyl residues.
[0014] In the multilayer polyimide film according to one embodiment of the present invention, the adhesive layer is disposed on both surfaces of the non-thermoplastic polyimide layer.
[0015] In the multilayer polyimide film according to one embodiment of the present invention, the adhesive layer contains a tertiary amine at a content of 1 mass ppm or more.
[0016] In the multilayer polyimide film according to one embodiment of the present invention, the non-thermoplastic polyimide layer contains a tertiary amine at a content of 1 mass ppm or more.
[0017] In the multilayer polyimide film described in one embodiment of the present invention, the non-thermoplastic polyimide contained in the aforementioned non-thermoplastic polyimide layer has one or more tetracarboxylic dianhydride residues selected from the group consisting of 3,3',4,4'-biphenyltetracarboxylic dianhydride residues and 4,4'-oxydiphthalic anhydride residues, and one or more diamine residues selected from the group consisting of p-phenylenediamine residues and 1,3-bis(4-aminophenoxy)benzene residues.
[0018] In the multilayer polyimide film according to one embodiment of the present invention, the non-thermoplastic polyimide contained in the non-thermoplastic polyimide layer has a p-phenylenediamine residue, and the polyimide contained in the adhesive layer does not have a p-phenylenediamine residue.
[0019] In the multilayer polyimide film according to one embodiment of the present invention, the adhesive layer does not have a melting peak within a temperature range of 100° C. to 420° C.
[0020] The metal-clad laminate of the present invention comprises the multilayer polyimide film of the present invention and a metal layer disposed on a principal surface of at least one of the adhesive layers of the multilayer polyimide film.
[0021] The method for producing a multilayer polyimide film of the present invention comprises a non-thermoplastic polyimide layer and an adhesive layer disposed on at least one side of the non-thermoplastic polyimide layer, wherein the adhesive layer comprises polyimide. The method comprises a coating step, a gel film forming step, and an imidization step. In the coating step, a non-thermoplastic polyimide layer forming solution comprising polyamic acid, acetic anhydride, and a tertiary amine and an adhesive layer forming solution comprising polyamic acid are coated on a support by a coextrusion-cast coating method. In the gel film forming step, the coating film obtained in the coating step is dried to form a self-supporting gel film. In the imidization step, the gel film obtained in the gel film forming step is heated at a maximum temperature of 360° C. or higher to imidize the polyamic acid in the non-thermoplastic polyimide layer forming solution and the polyamic acid in the adhesive layer forming solution. In the coating step, the polyamic acid contained in the adhesive layer-forming solution has a pyromellitic dianhydride residue, a 3,3',4,4'-biphenyltetracarboxylic dianhydride residue, a 1,3-bis(4-aminophenoxy)benzene residue, and a 4,4'-diamino-2,2'-dimethylbiphenyl residue. In the coating step, the polyamic acid contained in the non-thermoplastic polyimide layer-forming solution has one or more tetracarboxylic dianhydride residues selected from the group consisting of 3,3',4,4'-biphenyltetracarboxylic dianhydride residue and 4,4'-oxydiphthalic anhydride residue, and one or more diamine residues selected from the group consisting of a p-phenylenediamine residue and a 1,3-bis(4-aminophenoxy)benzene residue.
[0022] In the method for producing a multilayer polyimide film according to one embodiment of the present invention, in the coating step, the polyamic acid contained in the non-thermoplastic polyimide layer-forming solution has a p-phenylenediamine residue, and the polyamic acid contained in the adhesive layer-forming solution does not have a p-phenylenediamine residue.
[0023] In the method for producing a multilayer polyimide film according to one embodiment of the present invention, in the imidization step, the heating time of the gel film at the maximum temperature is 10 seconds to 300 seconds.
[0024] In the method for producing a multilayer polyimide film according to one embodiment of the present invention, the adhesive layer has no melting peak within a temperature range of 100° C. to 420° C., or has a melting heat of 1.0 J / g or less.
[0025] In the method for producing a multilayer polyimide film according to one embodiment of the present invention, the adhesive layer does not have a melting peak within a temperature range of 100° C. to 420° C.
[0026] In the method for producing a multilayer polyimide film according to one embodiment of the present invention, the non-thermoplastic polyimide layer has a dielectric loss tangent of 0.0030 or less at a frequency of 10 GHz, a temperature of 23° C., and a relative humidity of 50%.
[0027] Effects of the Invention
[0028] The present invention provides a multilayer polyimide film having excellent productivity while ensuring adhesion to a metal layer and reducing dielectric loss tangent, and a method for producing the same; and a metal-clad laminate obtained using the multilayer polyimide film. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a cross-sectional view showing an example of the multilayer polyimide film according to the present invention.
[0030] Figure 2 This is a cross-sectional view showing an example of the metal foil-clad laminate according to the present invention. DETAILED DESCRIPTION
[0031] Hereinafter, preferred embodiments of the present invention will be described in detail, but the present invention is not limited thereto. In addition, all academic documents and patent documents described in this specification are incorporated herein by reference.
[0032] First, the terms used in this specification are explained. "Constitutional unit" refers to a repeating unit that constitutes a polymer. "Polyimide" is a polymer containing a structural unit represented by the following general formula (1) (hereinafter sometimes referred to as "structural unit (1)").
[0033]
[0034] In the general formula (1), X 1 represents a tetracarboxylic dianhydride residue (a tetravalent organic group derived from tetracarboxylic dianhydride), X 2 represents a diamine residue (a divalent organic group derived from a diamine).
[0035] The content of the structural unit (1) relative to all the structural units constituting the polyimide is, for example, 50 mol% to 100 mol%, preferably 60 mol% to 100 mol%, more preferably 70 mol% to 100 mol%, further preferably 80 mol% to 100 mol%, further preferably 90 mol% to 100 mol%, and can be 100 mol%.
[0036] "Polyamic acid" is a polymer containing a structural unit represented by the following general formula (2) (hereinafter sometimes referred to as "structural unit (2)").
[0037]
[0038] In the general formula (2), A 1 represents a tetracarboxylic dianhydride residue (a tetravalent organic group derived from tetracarboxylic dianhydride), A 2 represents a diamine residue (a divalent organic group derived from a diamine).
[0039] The content of the structural unit (2) relative to all the structural units constituting the polyamic acid is, for example, 50 mol% to 100 mol%, preferably 60 mol% to 100 mol%, more preferably 70 mol% to 100 mol%, further preferably 80 mol% to 100 mol%, further preferably 90 mol% to 100 mol%, and can be 100 mol%.
[0040] Polyimide is an imide of polyamic acid. Therefore, when the content of structural unit (2) relative to all structural units constituting polyamic acid is 100 mol%, the polyimide as the imide of polyamic acid has A in the general formula (2). 1 The residue shown is used as X in the general formula (1) 1 , and having A in general formula (2) 2 The residue shown is used as X in the general formula (1) 2 .
[0041] The "dielectric loss tangent" is the dielectric loss tangent at a frequency of 10 GHz, a temperature of 23° C., and a relative humidity of 50%. The dielectric loss tangent is measured by the same method as in the examples described below or a method based thereon.
[0042] The “non-thermoplastic polyimide” refers to a polyimide that maintains a thin film shape (flat film shape) when fixed to a metal fixing frame in a thin film state and heated at a heating temperature of 380° C. for 2 minutes.
[0043] The "main surface" of a layered object (more specifically, a non-thermoplastic polyimide layer, an adhesive layer, a multilayer polyimide film, a metal layer, etc.) refers to a surface perpendicular to the thickness direction of the layered object.
[0044] Hereinafter, the compound name may be followed by "system" to collectively refer to the compound and its derivatives. Tetracarboxylic dianhydride may be referred to as "acid dianhydride." Adhesion properties to metal layers may be abbreviated as "adhesion properties."
[0045] The drawings referred to in the following description schematically illustrate various components for ease of understanding. For ease of illustration, the sizes, numbers, shapes, and other aspects of the components shown may differ from the actual components. Furthermore, for ease of explanation, components identical to those in previously described drawings may be designated with the same reference numerals in subsequent drawings, and their descriptions may be omitted.
[0046] Hereinafter, preferred embodiments of the present invention will be described in the order of a method for producing a multilayer polyimide film, a multilayer polyimide film, and a metal foil-clad laminate.
[0047] <First Embodiment: Method for Manufacturing Multilayer Polyimide Film>
[0048] In the manufacturing method of the multilayer polyimide film described in the first embodiment of the present invention, the multilayer polyimide film has a non-thermoplastic polyimide layer and an adhesive layer configured on at least one side of the non-thermoplastic polyimide layer, the adhesive layer comprising polyimide, and the manufacturing method is equipped with a coating process, a gel film forming process and an imidization process. In the coating process, a non-thermoplastic polyimide layer forming solution comprising polyamic acid, acetic anhydride and tertiary amine and an adhesive layer forming solution comprising polyamic acid are coated on a support by a coextrusion-cast coating method. In the gel film forming process, the coating film obtained in the coating process is dried to form a self-supporting gel film. In the imidization process, the gel film obtained in the gel film forming process is heated under conditions of a maximum temperature of 360°C or more, so that the polyamic acid in the non-thermoplastic polyimide layer forming solution and the polyamic acid in the adhesive layer forming solution are imidized. In the coating step, the polyamic acid contained in the adhesive layer-forming solution has a pyromellitic dianhydride residue, a 3,3',4,4'-biphenyltetracarboxylic dianhydride residue, a 1,3-bis(4-aminophenoxy)benzene residue, and a 4,4'-diamino-2,2'-dimethylbiphenyl residue. In the coating step, the polyamic acid contained in the non-thermoplastic polyimide layer-forming solution has one or more tetracarboxylic dianhydride residues selected from the group consisting of 3,3',4,4'-biphenyltetracarboxylic dianhydride residue and 4,4'-oxydiphthalic anhydride residue, and one or more diamine residues selected from the group consisting of a p-phenylenediamine residue and a 1,3-bis(4-aminophenoxy)benzene residue.
[0049] The aforementioned "coextrusion-cast coating method" is a method for forming a coating film using an extrusion molding machine equipped with a two-layer or more extrusion molding die. Specifically, the coextrusion-cast coating method is a method in which a non-thermoplastic polyimide layer-forming solution and an adhesive layer-forming solution are extruded from the lip opening of the extrusion molding die into a two-layer or more film, thereby forming a coating film having a two-layer or more layer structure on a support.
[0050] Hereinafter, a self-supporting gel film may be abbreviated as a "gel film". Pyromellitic dianhydride may be referred to as "PMDA". 3,3',4,4'-biphenyltetracarboxylic dianhydride may be referred to as "BPDA". 1,3-bis(4-aminophenoxy)benzene may be referred to as "TPE-R". 4,4'-diamino-2,2'-dimethylbiphenyl may be referred to as "m-TB". Paraphenylenediamine may be referred to as "PDA". 4,4'-oxydiphthalic anhydride may be referred to as "ODPA". The non-thermoplastic polyimide contained in the non-thermoplastic polyimide layer may be abbreviated as "non-thermoplastic polyimide".
[0051] The method for producing a multilayer polyimide film according to the first embodiment can produce a multilayer polyimide film that can improve productivity, ensure adhesion to a metal layer, and reduce dielectric loss tangent. The reason for this is presumably as follows.
[0052] The manufacturing method of the first embodiment employs a coextrusion-cast coating method and a method (chemical imidization method) that uses acetic anhydride and a tertiary amine to promote imidization. This simplifies the film formation process and shortens the imidization time. Therefore, the manufacturing method of the multilayer polyimide film of the first embodiment can improve productivity.
[0053] In addition, in the first embodiment, the polyamic acid included in the solution for forming the non-thermoplastic polyimide layer has one or more acid dianhydride residues selected from the group consisting of BPDA residues and ODPA residues and one or more diamine residues selected from the group consisting of PDA residues and TPE-R residues, and the polyamic acid is imidized by a chemical imidization method under the condition that the maximum temperature is more than 360 ° C. In the case of adopting a chemical imidization method, the imidization reaction proceeds rapidly compared with the thermal imidization method. Therefore, in the first embodiment, the imidization reaction of the polyamic acid is carried out in a state where the amount of solvent is relatively large. In the first embodiment, the polyamic acid with the above-mentioned specific residue is imidized by a chemical imidization method under the condition that the maximum temperature is more than 360 ° C. Therefore, the filling (packing) property of the obtained non-thermoplastic polyimide becomes higher. As a result, there is a tendency for the dielectric loss tangent to become lower in the non-thermoplastic polyimide layer obtained by the manufacturing method described in the first embodiment. Therefore, according to the method for manufacturing a multilayer polyimide film according to the first embodiment, the dielectric loss tangent of the multilayer polyimide film can be reduced.
[0054] Furthermore, in the first embodiment, the polyamic acid contained in the adhesive layer-forming solution has PMDA residues, BPDA residues, TPE-R residues, and m-TB residues. Therefore, when imidization is performed at a maximum temperature of 360°C or higher, the adhesive properties of the resulting adhesive layer are not degraded, and the shape of the film containing the polyamic acid in the adhesive layer-forming solution can be well maintained. Therefore, the method for producing a multilayer polyimide film according to the first embodiment can ensure excellent adhesion to the metal layer.
[0055] In the first embodiment, in order to obtain a multilayer polyimide film that can improve the adhesion properties with the metal layer and further reduce the dielectric loss tangent, it is preferred that: the polyamic acid contained in the solution for forming the non-thermoplastic polyimide layer has a PDA residue, and the polyamic acid contained in the solution for forming the adhesive layer does not have a PDA residue.
[0056] Hereinafter, each step included in the production method described in the first embodiment will be described in detail.
[0057] [Coating process]
[0058] (Solution for forming non-thermoplastic polyimide layer)
[0059] The non-thermoplastic polyimide layer forming solution is a solution for forming a non-thermoplastic polyimide layer as a core layer of a multilayer polyimide film. The non-thermoplastic polyimide layer forming solution contains polyamic acid, acetic anhydride, and a tertiary amine.
[0060] The polyamic acid (hereinafter sometimes referred to as "non-thermoplastic polyamic acid") contained in the solution for forming a non-thermoplastic polyimide layer has one or more dianhydride residues selected from the group consisting of BPDA residues and ODPA residues, and one or more diamine residues selected from the group consisting of PDA residues and TPE-R residues. The non-thermoplastic polyamic acid may contain one or more polyamic acids, but is preferably composed of one polyamic acid.
[0061] The non-thermoplastic polyamic acid may further have other acid dianhydride residues on the basis of having one or more acid dianhydride residues selected from the group consisting of BPDA residues and ODPA residues. As acid dianhydrides (monomers) for forming other acid dianhydride residues (acid dianhydride residues other than BPDA residues and ODPA residues), for example, PMDA, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 3, 4'-oxydiphthalic anhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, p-phenylenebis(trimellitic acid monoester anhydride), ethylenebis(trimellitic acid monoester anhydride), bisphenol A bis(trimellitic acid monoester anhydride) and derivatives thereof, etc.
[0062] In order to obtain a multilayer polyimide film capable of improving heat resistance and further reducing dielectric loss tangent, the other acid dianhydride residue is preferably a PMDA residue.
[0063] In order to obtain a multilayer polyimide film capable of further reducing the dielectric loss tangent, the total content of BPDA residues and ODPA residues relative to all the acid dianhydride residues constituting the non-thermoplastic polyamic acid is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, further preferably 90 mol% or more, and can be 100 mol%.
[0064] When PMDA residues are used as other acid dianhydride residues, in order to obtain a multilayer polyimide film capable of improving heat resistance and further reducing dielectric loss tangent, the total content of BPDA residues, ODPA residues and PMDA residues relative to all acid dianhydride residues constituting the non-thermoplastic polyamic acid is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, even more preferably 90 mol% or more, particularly preferably 95 mol% or more, and may be 100 mol%.
[0065] In order to obtain a multilayer polyimide film capable of further reducing the dielectric loss tangent, the non-thermoplastic polyamic acid preferably has two acid dianhydride residues, namely, BPDA residue and ODPA residue. In order to obtain a multilayer polyimide film capable of improving heat resistance and further reducing the dielectric loss tangent, the non-thermoplastic polyamic acid preferably has three acid dianhydride residues, namely, BPDA residue, ODPA residue and PMDA residue.
[0066] In order to obtain a multilayer polyimide film capable of further reducing the dielectric loss tangent, the content of BPDA residues relative to all acid dianhydride residues constituting the non-thermoplastic polyamic acid is preferably 40 mol% to 80 mol%, more preferably 50 mol% to 70 mol%.
[0067] In order to obtain a multilayer polyimide film capable of further reducing the dielectric loss tangent, the content of ODPA residues relative to all acid dianhydride residues constituting the non-thermoplastic polyamic acid is preferably 10 mol% to 50 mol%, more preferably 20 mol% to 40 mol%.
[0068] In order to obtain a multilayer polyimide film that can improve heat resistance and further reduce dielectric loss tangent, the content of PMDA residues relative to all acid dianhydride residues constituting the non-thermoplastic polyamic acid is preferably 1 mol% to 10 mol%, more preferably 2 mol% to 8 mol%.
[0069] The non-thermoplastic polyamic acid has, in addition to the acid dianhydride residues, one or more diamine residues selected from the group consisting of PDA residues and TPE-R residues.
[0070] The non-thermoplastic polyamic acid may further have another diamine residue in addition to having one or more diamine residues selected from the group consisting of PDA residues and TPE-R residues. Examples of the diamine (monomer) for forming other diamine residues (diamine residues other than PDA residues and TPE-R residues) include 1,4-bis(4-aminophenoxy)benzene, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,5-diaminonaphthalene, 4,4'-diaminodiphenyldiethylsilane, 4,4'-diaminodiphenylsilane, 4,4'-diaminodiphenylethylphosphine oxide, 4,4'-diaminodiphenyl N-methylamine, 4,4'-diaminodiphenyl N-phenylamine, 1,3-diaminobenzene, 1,2-diaminobenzene, and derivatives thereof.
[0071] In order to obtain a multilayer polyimide film capable of further reducing the dielectric loss tangent, the total content of PDA residues and TPE-R residues relative to all diamine residues constituting the non-thermoplastic polyamic acid is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, even more preferably 90 mol% or more, particularly preferably 95 mol% or more, and may be 100 mol%.
[0072] In order to obtain a multilayer polyimide film capable of further reducing the dielectric loss tangent, the non-thermoplastic polyamic acid preferably has two types of diamine residues, namely, a PDA residue and a TPE-R residue.
[0073] In order to obtain a multilayer polyimide film capable of further reducing the dielectric loss tangent, the content of the PDA residue relative to all diamine residues constituting the non-thermoplastic polyamic acid is preferably 60 mol% to 95 mol%, more preferably 70 mol% to 90 mol%.
[0074] In order to obtain a multilayer polyimide film capable of further reducing the dielectric loss tangent, the content of the TPE-R residue is preferably 5 mol% to 40 mol%, more preferably 10 mol% to 30 mol%, relative to the total diamine residues constituting the non-thermoplastic polyamic acid.
[0075] As the manufacture method (synthetic method) of non-thermoplastic polyamic acid, all known methods and the method for combining them can be used.As the specific example of the manufacture method (synthetic method) of non-thermoplastic polyamic acid, a method for reacting diamines with tetracarboxylic dianhydride in an organic solvent can be listed. The amount of substance of diamines during reaction is preferably substantially equal to the amount of substance of tetracarboxylic dianhydride. In the case of using diamines and tetracarboxylic dianhydride to synthesize non-thermoplastic polyamic acid, by adjusting the amount of substance of diamines (when using multiple diamines, the amount of substance of each diamine) and the amount of substance of tetracarboxylic dianhydride (when using multiple tetracarboxylic dianhydride, the amount of substance of each tetracarboxylic dianhydride), it is possible to obtain desired polyamic acid (polymer of diamines and tetracarboxylic dianhydride). The mole fraction of each residue in non-thermoplastic polyamic acid is, for example, identical with the mole fraction of each monomer (diamines and tetracarboxylic dianhydride) for synthesizing non-thermoplastic polyamic acid. The temperature conditions for the reaction of the diamine and tetracarboxylic dianhydride, i.e., the synthesis reaction of the non-thermoplastic polyamic acid, are not particularly limited, but are, for example, in the range of 10°C to 150°C. The reaction time for the synthesis reaction of the non-thermoplastic polyamic acid is, for example, in the range of 10 minutes to 30 hours. Any monomer addition method can be used in the synthesis of the non-thermoplastic polyamic acid.
[0076] The non-thermoplastic polyimide layer forming solution further includes acetic anhydride as a dehydration ring-closing agent and a tertiary amine as a catalyst on the basis of including non-thermoplastic polyamic acid. By making the non-thermoplastic polyimide layer forming solution include acetic anhydride and a tertiary amine, imidization is promoted. As tertiary amine, for example, aliphatic tertiary amine, aromatic tertiary amine, heterocyclic tertiary amine, etc. can be listed. In order to easily promote imidization, as a tertiary amine, preferably a heterocyclic tertiary amine, more preferably selected from the group consisting of a pyridine compound (more specifically β-picoline, γ-picoline, 3,5-lutidine, etc.) having an alkyl group introduced at the β position and / or γ position, pyridine and isoquinoline.
[0077] As the addition of tertiary amine, relative to the amide group of non-thermoplastic polyamic acid, preferably more than 0.5 times of molar equivalent and less than 5.0 times of molar equivalent, more preferably more than 0.7 times of molar equivalent and less than 2.5 times of molar equivalent, more preferably more than 0.8 times of molar equivalent and less than 2.0 times of molar equivalent. In addition, as the addition of acetic anhydride, relative to the amide group of non-thermoplastic polyamic acid, preferably more than 0.5 times of molar equivalent and less than 10.0 times of molar equivalent, more preferably more than 0.7 times of molar equivalent and less than 5.0 times of molar equivalent, more preferably more than 0.8 times of molar equivalent and less than 3.0 times of molar equivalent. It should be noted that, in this specification, " amide group of non-thermoplastic polyamic acid " refers to the amide group generated by the polymerization reaction of diamine and tetracarboxylic dianhydride. When adding tertiary amine and acetic anhydride in the polyamic acid solution described later, it is possible to directly add and be insoluble in an organic solvent, or it is possible to add a mixture obtained by dissolving it in an organic solvent. In the method of directly adding the polyamide without dissolving it in an organic solvent, the tertiary amine and acetic anhydride may react vigorously to form a gel before they diffuse. Therefore, it is preferable to add a solution (imidation accelerator) obtained by dissolving the tertiary amine and acetic anhydride in an organic solvent to the polyamic acid solution.
[0078] The solution for forming a non-thermoplastic polyimide layer is obtained by, for example, adding a tertiary amine and acetic anhydride to a polyamic acid solution containing a non-thermoplastic polyamic acid and an organic solvent. Examples of organic solvents that can be used in the polyamic acid solution include urea solvents such as tetramethylurea and N,N-dimethylethylurea; sulfoxide solvents such as dimethyl sulfoxide; sulfone solvents such as diphenylsulfone and tetramethylsulfone; amide solvents such as N,N-dimethylacetamide, N,N-dimethylformamide (hereinafter sometimes referred to as "DMF"), N,N-diethylacetamide, N-methyl-2-pyrrolidone, and hexamethylphosphorus triamide; ester solvents such as γ-butyrolactone; alkyl halide solvents such as chloroform and dichloromethane; aromatic hydrocarbon solvents such as benzene and toluene; phenolic solvents such as phenol and cresol; ketone solvents such as cyclopentanone; and ether solvents such as tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, dimethyl ether, diethyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, and p-cresol methyl ether. These solvents are generally used alone, but two or more may be used in combination as needed. In the case of obtaining non-thermoplastic polyamic acid by above-mentioned polymerization method, reaction soln (reacted solution) itself can be used as polyamic acid solution.In this case, the organic solvent in the polyamic acid solution is the organic solvent used in reaction in the above-mentioned polymerization method.In addition, the non-thermoplastic polyamic acid of the solid that can be removed from reaction soln and obtained by solvent can be dissolved in organic solvent and prepare polyamic acid solution.
[0079] Can add additives such as dye, surfactant, leveling agent, plasticizer, organosilicon, sensitizer in polyamic acid solution.In addition, for the purpose of improving the various characteristics of films such as slippage, thermal conductivity, electrical conductivity, corona resistance, ring stiffness (loop stiffness), also can add filler in polyamic acid solution.As filler, can use any filler, as preferred example, can enumerate the filler formed by silicon dioxide, titanium oxide, aluminum oxide, silicon nitride, boron nitride, calcium hydrogen phosphate, calcium phosphate, mica etc.
[0080] The concentration of the non-thermoplastic polyamic acid in the polyamic acid solution is not particularly limited, but is, for example, 5 wt % to 35 wt %, and preferably 8 wt % to 30 wt %, based on the total amount of the polyamic acid solution.
[0081] (Adhesive layer forming solution)
[0082] The bonding layer forming solution is a solution for forming a bonding layer that is bonded to the metal layer. The bonding layer forming solution contains polyamic acid. In addition to containing polyamic acid, the bonding layer forming solution may also contain the above-mentioned acetic anhydride and tertiary amine. When the bonding layer forming solution contains acetic anhydride and tertiary amine, the preferred addition amounts of acetic anhydride and tertiary amine are the same as the preferred addition amounts in the above-mentioned non-thermoplastic polyimide layer forming solution. It should be noted that if the non-thermoplastic polyimide layer forming solution contains acetic anhydride and tertiary amine, even if the bonding layer forming solution does not contain acetic anhydride and tertiary amine, in the imidization process, acetic anhydride and tertiary amine will diffuse from the non-thermoplastic polyimide layer forming solution to the bonding layer forming solution. Therefore, the polyamic acid in the bonding layer forming solution can be imidized by a chemical imidization method.
[0083] The polyamic acid contained in the adhesive layer forming solution (hereinafter sometimes referred to as "adhesive polyamic acid") has PMDA residues, BPDA residues, TPE-R residues, and m-TB residues. The adhesive polyamic acid may contain one or two or more polyamic acids, but is preferably composed of one polyamic acid.
[0084] Adhesive polyamic acid can also have other acid dianhydride residues on the basis of having PMDA residue and BPDA residue.As the acid dianhydride (monomer) for forming other acid dianhydride residues (acid dianhydride residue except PMDA residue and BPDA residue), for example, can enumerate the acid dianhydride identical with the material illustrated as the acid dianhydride for forming above-mentioned non-thermoplastic polyamic acid.
[0085] In order to obtain a multilayer polyimide film with further reduced dielectric loss tangent and better adhesive properties, the total content of PMDA residues and BPDA residues relative to all acid dianhydride residues constituting the adhesive polyamic acid is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, further preferably 90 mol% or more, particularly preferably 95 mol% or more, and can be 100 mol%.
[0086] In order to obtain a multilayer polyimide film with further reduced dielectric loss tangent and better adhesive properties, the content of PMDA residues relative to all acid dianhydride residues constituting the adhesive polyamic acid is preferably 20 mol% to 80 mol%, more preferably 30 mol% to 70 mol%.
[0087] In order to obtain a multilayer polyimide film with a further reduced dielectric loss tangent and better adhesive properties, the content of BPDA residues relative to all acid dianhydride residues constituting the adhesive polyamic acid is preferably 20 mol% to 80 mol%, more preferably 30 mol% to 70 mol%.
[0088] The adhesive polyamic acid has, in addition to the above-mentioned acid dianhydride residue, a TPE-R residue and an m-TB residue as diamine residues.
[0089] The adhesive polyamic acid may have other diamine residues in addition to TPE-R residues and m-TB residues. Examples of the diamine (monomer) used to form the other diamine residues (diamine residues other than TPE-R residues and m-TB residues) include the same diamines exemplified as those used to form the above-mentioned non-thermoplastic polyamic acid.
[0090] In order to obtain a multilayer polyimide film with a further reduced dielectric loss tangent and further excellent adhesive properties, the total content of TPE-R residues and m-TB residues relative to all diamine residues constituting the adhesive polyamic acid is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, even more preferably 90 mol% or more, particularly preferably 95 mol% or more, and may be 100 mol%.
[0091] In order to obtain a multilayer polyimide film with a further reduced dielectric loss tangent and better adhesive properties, the content of TPE-R residues relative to all diamine residues constituting the adhesive polyamic acid is preferably 50 mol% to 95 mol%, more preferably 60 mol% to 95 mol%.
[0092] In order to obtain a multilayer polyimide film with a further reduced dielectric loss tangent and better adhesive properties, the content of m-TB residues relative to all diamine residues constituting the adhesive polyamic acid is preferably 5 mol% to 50 mol%, more preferably 5 mol% to 40 mol%.
[0093] Additives such as dyes, surfactants, leveling agents, plasticizers, organosilicones, and sensitizers may be added to the adhesive layer-forming solution. Furthermore, fillers may be added to the adhesive layer-forming solution to improve various film properties such as slip, thermal conductivity, electrical conductivity, corona resistance, and ring stiffness. Any filler may be used, and preferred examples include fillers composed of silicon dioxide, titanium oxide, aluminum oxide, silicon nitride, boron nitride, calcium hydrogen phosphate, calcium phosphate, and mica.
[0094] The method for obtaining the adhesive layer forming solution (polyamic acid solution) is the same as the method for obtaining the non-thermoplastic polyimide layer forming solution except that an adhesive polyamic acid is synthesized instead of the non-thermoplastic polyamic acid (a monomer for synthesizing the adhesive polyamic acid is used).
[0095] The concentration of the adhesive polyamic acid in the adhesive layer forming solution (polyamic acid solution) is not particularly limited, and is, for example, 5 wt % to 35 wt %, and preferably 8 wt % to 30 wt %, based on the total amount of the adhesive layer forming solution.
[0096] In order to obtain a multilayer polyimide film with further reduced dielectric loss tangent and better adhesion properties, the method for producing a multilayer polyimide film according to the first embodiment preferably satisfies the following condition 1, more preferably satisfies the following conditions 1 and 2, and even more preferably satisfies the following conditions 1, 2, and 3.
[0097] Condition 1: The adhesive polyamic acid has only a PMDA residue and a BPDA residue as acid dianhydride residues, and has only a TPE-R residue and an m-TB residue as diamine residues.
[0098] Condition 2: The non-thermoplastic polyamic acid has only BPDA residues, ODPA residues, and PMDA residues as acid dianhydride residues, and only TPE-R residues and PDA residues as diamine residues.
[0099] Condition 3: In the adhesive polyamic acid, the value obtained by dividing the amount of PMDA residues by the amount of BPDA residues is 0.8 to 1.2, and the value obtained by dividing the amount of TPE-R residues by the amount of m-TB residues is 2.0 to 2.5.
[0100] If the above conditions 1 and 2 are satisfied, both the polyimide contained in the non-thermoplastic polyimide layer and the polyimide contained in the adhesive layer have TPE-R residues, PMDA residues, and BPDA residues. Therefore, a multilayer polyimide film having excellent adhesion between the non-thermoplastic polyimide layer and the adhesive layer can be obtained.
[0101] (Coating method)
[0102] The coating method in the coating step is not particularly limited as long as the non-thermoplastic polyimide layer-forming solution and the adhesive layer-forming solution are coated on the support by a coextrusion-cast coating method. For example, a coating film having a layer structure of two or more layers can be formed on the support by extruding the non-thermoplastic polyimide layer-forming solution and the adhesive layer-forming solution from the lip opening of an extrusion die using a known extruder.
[0103] As the support used in the coextrusion-cast coating method, a glass plate, an aluminum foil, a stainless steel endless belt, a stainless steel cylinder, etc. can be preferably used.
[0104] [Gel film forming step]
[0105] In the gel film forming step, the coating film obtained in the coating step is dried to form a self-supporting gel film. The coating film can be dried, for example, on a support. The drying temperature for drying the coating film is, for example, 50°C to 200°C. The drying time for drying the coating film is, for example, 1 minute to 100 minutes. It should be noted that a multi-stage drying step can be provided, such as heating the coating film at 50°C for 10 minutes and then at 100°C for 10 minutes.
[0106] [Imidization step]
[0107] In the imidization process, the gel film obtained in the gel film forming process is heated under conditions of a maximum temperature of 360°C or more, so that the polyamic acid in the non-thermoplastic polyimide layer forming solution and the polyamic acid in the adhesive layer forming solution are imidized. Through this process, a laminate of a non-thermoplastic polyimide layer and an adhesive layer, i.e., a multilayer polyimide film, can be obtained. In order to further reduce the dielectric loss tangent, the maximum temperature in the imidization process is preferably 380°C or more. As the upper limit of the maximum temperature in the imidization process, for example, 500°C, preferably 450°C. In order to obtain a multilayer polyimide film with further reduced dielectric loss tangent and better bonding properties, the heating time of the gel film at the maximum temperature is preferably 10 seconds or more and 300 seconds or less, more preferably 20 seconds or more and 200 seconds or less, further preferably 30 seconds or more and 150 seconds or less, and can be 60 seconds or more and 100 seconds or less. In addition, any time can be maintained at any temperature until the maximum temperature is reached.
[0108] The imidization step can be performed in air, under reduced pressure, or in an inert gas such as nitrogen. Furthermore, to prevent shrinkage during film curing, it is preferable to peel the gel film from the support and heat it while securing the ends of the gel film. Furthermore, during the imidization step, the gel film can be stretched in the conveying direction or in a direction perpendicular to the conveying direction while being heated.
[0109] [Multilayer polyimide film obtained by the production method described in the first embodiment]
[0110] Next, the multilayer polyimide film obtained by the production method described in the first embodiment will be described with reference to the drawings.
[0111] Figure 1 1 is a cross-sectional view showing an example of a multilayer polyimide film obtained by the manufacturing method described in the first embodiment. Figure 1 As shown, the multilayer polyimide film 10 includes a non-thermoplastic polyimide layer 11 and an adhesive layer 12 disposed on at least one surface (one main surface) of the non-thermoplastic polyimide layer 11 .
[0112] It should be noted that in Figure 1In the multilayer polyimide film 10 shown, the adhesive layer 12 is provided only on one side of the non-thermoplastic polyimide layer 11. However, as in the multilayer polyimide film produced in the embodiments described below, the adhesive layer 12 may be provided on both sides (both main sides) of the non-thermoplastic polyimide layer 11. In the case where the adhesive layers 12 are provided on both sides of the non-thermoplastic polyimide layer 11, the two adhesive layers 12 may contain the same type of polyimide or different types of polyimides. In addition, the thickness of the two adhesive layers 12 may be the same or different. In addition, in the present invention, the non-thermoplastic polyimide layer 11 and the adhesive layer 12 may be provided in two or more layers. In the following description, the "multilayer polyimide film 10" includes: a film having an adhesive layer 12 only on one side of a non-thermoplastic polyimide layer 11, a film having an adhesive layer 12 on both sides of a non-thermoplastic polyimide layer 11, and a film having two or more layers of both a non-thermoplastic polyimide layer 11 and an adhesive layer 12.
[0113] The thickness of the multilayer polyimide film 10 (the total thickness of each layer) is, for example, 6 μm or more and 60 μm or less. The thinner the multilayer polyimide film 10 is, the easier it is to lightweight the resulting FPC, and the more improved the bendability of the resulting FPC is. In order to ensure mechanical strength and easily achieve lightweight FPC and improve the bendability of the FPC, the thickness of the multilayer polyimide film 10 is preferably 7 μm or more and 60 μm or less, more preferably 10 μm or more and 60 μm or less. The thickness of the multilayer polyimide film 10 can be measured using a laser hologram measuring instrument.
[0114] In order to ensure the adhesion with the metal foil and to easily realize the thinning of the FPC, the thickness of the adhesive layer 12 (when more than two layers of adhesive layers 12 are provided, the thickness of each adhesive layer 12) is preferably more than 1 μm and less than 15 μm. In addition, in order to easily adjust the linear expansion coefficient of the multilayer polyimide film 10, the thickness ratio of the non-thermoplastic polyimide layer 11 to the adhesive layer 12 (the thickness of the non-thermoplastic polyimide layer 11 / the thickness of the adhesive layer 12) is preferably more than 55 / 45 and less than 95 / 5. When the non-thermoplastic polyimide layer 11 and the adhesive layer 12 are respectively provided with multiple layers, the above-mentioned thickness ratio is the ratio of their respective total thicknesses. Even if the number of layers of the adhesive layer 12 increases, it is preferred that the total thickness of the adhesive layer 12 does not exceed the total thickness of the non-thermoplastic polyimide layer 11.
[0115] To suppress warping of the multilayer polyimide film 10, adhesive layers 12 are preferably provided on both sides of the non-thermoplastic polyimide layer 11. More preferably, adhesive layers 12 comprising the same polyimide are provided on both sides of the non-thermoplastic polyimide layer 11. When adhesive layers 12 are provided on both sides of the non-thermoplastic polyimide layer 11, the thicknesses of the two adhesive layers 12 are preferably the same to suppress warping of the multilayer polyimide film 10. It should be noted that even if the thicknesses of the two adhesive layers 12 differ, warping of the multilayer polyimide film 10 can be suppressed if the thickness of the other adhesive layer 12 is within a range of 40% or more and less than 100% of the thickness of the thicker adhesive layer 12.
[0116] In order to obtain a multilayer polyimide film 10 that can further reduce the dielectric loss tangent, the dielectric loss tangent of the non-thermoplastic polyimide layer 11 is preferably 0.0030 or less. The dielectric loss tangent of the non-thermoplastic polyimide layer 11 can be adjusted by, for example, changing at least one of the content of the residues constituting the non-thermoplastic polyamic acid and the maximum temperature in the imidization process. By adjusting the dielectric loss tangent of the non-thermoplastic polyimide layer 11 to 0.0030 or less, the dielectric loss tangent of the multilayer polyimide film 10 can be set to 0.0040 or less, for example. The lower limit of the dielectric loss tangent of the non-thermoplastic polyimide layer 11 is not particularly limited, and is, for example, 0.0001.
[0117] In order to obtain a multilayer polyimide film 10 that can ensure bonding properties and further reduce the dielectric loss tangent, it is preferred that the adhesive layer 12 does not have a melting peak or the melting heat of the melting peak is 1.0 J / g or less within a temperature range of 100°C or more and 420°C or less. Hereinafter, the melting peak within a temperature range of 100°C or more and 420°C or less is sometimes referred to as a "melting peak". The method for measuring the melting heat of the melting peak is the same method as that of the embodiments described later or a method based thereon. In the case where the adhesive layer 12 does not have a melting peak or the melting heat of the melting peak is 1.0 J / g or less, the shape of the film containing the polyamic acid in the adhesive layer forming solution can be well maintained in the imidization process. Therefore, by heating with a maximum temperature of 360°C or more in the imidization process, the low dielectric loss tangent of the multilayer polyimide film 10 can be performed and the shape of the adhesive layer 12 suitable for bonding to the metal layer can be maintained. If imidization is performed by a chemical imidization method, there is a tendency for the heat of fusion of the melting peak of the adhesive layer 12 to be lowered. In addition, the heat of fusion of the melting peak of the adhesive layer 12 can be adjusted by, for example, changing at least one of the content of each residue constituting the adhesive polyamic acid and the maximum temperature in the imidization step.
[0118] In order to obtain the multilayer polyimide film 10 that can ensure adhesive properties and further reduce the dielectric loss tangent, the adhesive layer 12 preferably does not have a melting peak.
[0119] The adhesive layer 12 preferably has a storage modulus of 20.0 MPa or greater at 400°C and a loss modulus of 4.0 MPa or greater at 400°C. If the storage modulus and loss modulus are within the above ranges, the adhesive layer 12 can withstand heating even at high temperatures. Preferably, the storage modulus is 30.0 MPa or greater, and the loss modulus is 5.0 MPa or greater.
[0120] In order to obtain a multilayer polyimide film 10 having excellent adhesive properties, the storage modulus of the adhesive layer 12 at a temperature of 360°C is preferably 1.0 GPa or less, and more preferably 0.1 GPa or less. When a metal foil-clad laminate is produced using the multilayer polyimide film 10, if the storage modulus of the adhesive layer 12 at a temperature of 360°C is 1.0 GPa or less, the adhesive layer 12 can be made to have excellent adhesion at the preferred lamination temperature (360°C or above) when the adhesive layer 12 and the metal foil are bonded together.
[0121] The storage elastic modulus and loss elastic modulus of the adhesive layer 12 are measured by the same method as in the examples described later or a method based thereon.
[0122] The adhesion strength described in the examples below is an indicator of the adhesion between the adhesive layer 12 and the metal layer. To obtain a multilayer polyimide film 10 having excellent adhesive properties, the adhesion strength described in the examples below is preferably 10 N / cm or more.
[0123] The non-thermoplastic polyimide layer 11 may contain components (additives) other than the non-thermoplastic polyimide. Examples of additives include dyes, surfactants, leveling agents, plasticizers, silicones, fillers, and sensitizers. The content of the non-thermoplastic polyimide in the non-thermoplastic polyimide layer 11 is, for example, 70% by weight or greater, preferably 80% by weight or greater, more preferably 90% by weight or greater, and may be 100% by weight, relative to the total weight of the non-thermoplastic polyimide layer 11.
[0124] The adhesive layer 12 may contain ingredients (additives) other than polyimide. Examples of additives include dyes, surfactants, leveling agents, plasticizers, silicones, fillers, and sensitizers. The content of polyimide in the adhesive layer 12 relative to the total weight of the adhesive layer 12 is, for example, 70% by weight or greater, preferably 80% by weight or greater, more preferably 90% by weight or greater, and may be 100% by weight.
[0125] The tertiary amine used as a catalyst in the non-thermoplastic polyimide layer 11 and the adhesive layer 12 is contained in a content of, for example, 1 mass ppm or more and 1000 mass ppm or less.
[0126] <Second embodiment: multilayer polyimide film>
[0127] Next, the multilayer polyimide film according to the second embodiment of the present invention is described. The multilayer polyimide film according to the second embodiment has a non-thermoplastic polyimide layer and an adhesive layer disposed on at least one side of the non-thermoplastic polyimide layer, wherein the adhesive layer comprises polyimide. The dielectric loss tangent of the non-thermoplastic polyimide layer at a frequency of 10 GHz, a temperature of 23°C, and a relative humidity of 50% is 0.0030 or less. The adhesive layer does not have a melting peak or the melting heat of the melting peak is 1.0 J / g or less in the range of a temperature of 100°C to 420°C. The polyimide contained in the adhesive layer has one or more tetracarboxylic dianhydride residues selected from the group consisting of PMDA residues and BPDA residues, and one or more diamine residues selected from the group consisting of TPE-R residues and m-TB residues. The multilayer polyimide film according to the second embodiment has the above-mentioned structure, thereby being able to ensure the bonding properties with the metal layer and reduce the dielectric loss tangent and having excellent productivity.
[0128] The multilayer polyimide film of the second embodiment can be manufactured using the method for manufacturing the multilayer polyimide film of the first embodiment. Therefore, in the following description, overlapping details with the first embodiment may be omitted. The following description focuses on the differences from the first embodiment.
[0129] In the multilayer polyimide film according to the second embodiment, the non-thermoplastic polyimide layer is not particularly limited as long as the dielectric loss tangent is 0.0030 or less. In the second embodiment, in order to easily adjust the dielectric loss tangent to 0.0030 or less, the non-thermoplastic polyimide contained in the non-thermoplastic polyimide layer preferably has one or more tetracarboxylic dianhydride residues selected from the group consisting of BPDA residues and ODPA residues, and one or more diamine residues selected from the group consisting of PDA residues and TPE-R residues.
[0130] In the multilayer polyimide film according to the second embodiment, the adhesive layer is not particularly limited as long as it satisfies the following conditions A and B.
[0131] Condition A: There is no melting peak within the temperature range of 100° C. to 420° C., or the heat of fusion of the melting peak is 1.0 J / g or less.
[0132] Condition B: The polyimide contained in the adhesive layer has one or more tetracarboxylic dianhydride residues selected from the group consisting of PMDA residues and BPDA residues, and one or more diamine residues selected from the group consisting of TPE-R residues and m-TB residues.
[0133] Among them, in the second embodiment, in order to easily obtain an adhesive layer satisfying the above-mentioned condition A, the adhesive layer preferably has a PMDA residue, a BPDA residue, a TPE-R residue, and an m-TB residue.
[0134] In addition, in the second embodiment, in order to easily adjust the dielectric loss tangent of the non-thermoplastic polyimide layer to below 0.0030 and easily obtain the adhesive layer that satisfies the above-mentioned condition A, it is preferred that: the non-thermoplastic polyimide contained in the non-thermoplastic polyimide layer has a PDA residue, and the polyimide contained in the adhesive layer does not have a PDA residue.
[0135] In the second embodiment, the preferred contents of the above-mentioned residues and the types of optional residues other than the above-mentioned residues are the same as those of the first embodiment.
[0136] The other aspects of the second embodiment are the same as those described in the above section [Multilayer polyimide film obtained by the production method described in the first embodiment].
[0137] <Third Embodiment: Metal Foil-Clad Laminate>
[0138] Next, the metal-clad laminate according to the third embodiment of the present invention will be described with reference to the accompanying drawings. The metal-clad laminate according to the third embodiment comprises the multilayer polyimide film according to the second embodiment, and a metal layer disposed on the principal surface of at least one adhesive layer of the multilayer polyimide film. The metal-clad laminate according to the third embodiment can be manufactured using the multilayer polyimide film according to the second embodiment as a material. Therefore, in the following description, the description of the content that overlaps with the first and second embodiments may be omitted.
[0139] Figure 2 : is a cross-sectional view showing an example of the metal-clad laminate according to the third embodiment. Figure 2 As shown, the metal foil-clad laminate 20 includes a multilayer polyimide film 10 and a metal layer 13 (metal foil) disposed on the main surface 12 a of the adhesive layer 12 of the multilayer polyimide film 10 .
[0140] [Method for Manufacturing Metal-Clad Laminate According to Third Embodiment]
[0141] When the metal foil-clad laminate 20 is manufactured using the multilayer polyimide film 10, at least one surface (e.g., Figure 2 In the case of the non-thermoplastic polyimide layer 11, the main surface 12a of the adhesive layer 12 is bonded to the metal foil of the metal layer 13. Figure 2 The metal foil-clad laminate 20 shown is shown. The method for laminating the metal foil to the main surface 12a of the adhesive layer 12 is not particularly limited, and various known methods can be employed. For example, a hot roll laminating apparatus having one or more pairs of metal rolls or a continuous processing method using double belt press (DBP) can be employed. The specific configuration of the hot roll lamination method is not particularly limited, but to improve the appearance of the resulting metal foil-clad laminate 20, a protective material is preferably disposed between the pressurized surface and the metal foil.
[0142] When the adhesive layer 12 is provided on both surfaces of the non-thermoplastic polyimide layer 11 , a double-sided metal foil-clad laminate (not shown) is obtained by laminating metal foil to both surfaces (both main surfaces) of the multilayer polyimide film 10 .
[0143] The metal foil forming the metal layer 13 is not particularly limited, and any metal foil can be used. Suitable metal foils include, for example, copper, stainless steel, nickel, aluminum, and alloys of these metals. While rolled copper foil, electrolytic copper foil, and other copper foils are commonly used in conventional metal-clad laminates, copper foil is also preferably used in the third embodiment.
[0144] In addition, the metal foil may be one that has been subjected to surface treatment, etc., to adjust the surface roughness, etc., depending on the intended purpose. Furthermore, a rust-proof layer, a heat-resistant layer, an adhesive layer, etc. may be formed on the surface of the metal foil. There are no particular restrictions on the thickness of the metal foil, as long as it is a thickness that can fully function according to its intended use. To prevent wrinkles when laminating to the multilayer polyimide film 10 and facilitate thinning of the FPC, the thickness of the metal foil is preferably 5 μm to 50 μm.
[0145] Example
[0146] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited to these Examples.
[0147] <Measurement and Evaluation Methods of Physical Properties>
[0148] [Film-forming properties]
[0149] An imidization accelerator containing acetic anhydride / isoquinoline / DMF (weight ratio: acetic anhydride / isoquinoline / DMF=3.0 / 1.2 / 4.4) is added to a polyamic acid solution (specifically, any one of the polyamic acid solutions P4 to P13 described later) to obtain a solution for forming an adhesive layer. The amount of the imidization accelerator added is 50 parts by weight relative to 100 parts by weight of the polyamic acid solution. The obtained adhesive layer forming solution is stirred with a mixer while being extruded from a T-die of a film-making device and cast on an endless belt made of stainless steel to form a coating film. After the obtained coating film is dried at a temperature of 130°C for 100 seconds, the obtained gel film is peeled off from the endless belt and fixed to the clamp of a tenter. Subsequently, the gel film is heated at a temperature of 250°C for 17 seconds and then at a temperature of 300°C for 137 seconds to imidize the polyamic acid in the gel film. In the imidization step, a case where a single-layer film consisting of an adhesive layer with a thickness of 17 μm was obtained was recorded as “film formation possible”, and a case where wrinkles, cracks, or other problems occurred and film formation could not be achieved was recorded as “film formation impossible”.
[0150] [Melting temperature and melting heat of adhesive layer]
[0151] The melting temperature and heat of fusion were measured using a differential scanning calorimeter ("DSC220" manufactured by Seiko Instruments Inc.) using a measurement sample (mass: 8 mg) taken from the adhesive layer of the multilayer polyimide film obtained in the examples and comparative examples described below. Specifically, the measurement sample was placed in an aluminum dish (aluminum container) and the dish was placed in the measurement section of the differential scanning calorimeter. An empty aluminum dish was used as a reference. The atmosphere temperature was then raised from 0°C to 450°C at a heating rate of 10°C / min, and then lowered from 450°C to 0°C at a cooling rate of 40°C / min. Subsequently, the temperature was raised from 0°C to 450°C again at a heating rate of 10°C / min. The temperature of the peak of the endothermic spectrum during the second heating was taken as the melting temperature. The heat of fusion (unit: J / g) was determined based on the area of the peak of the endothermic spectrum. It should be noted that when there is no melting peak in the temperature range of 100°C to 420°C in the above-mentioned endothermic spectrum, in other words, when the adhesive layer as the measurement object does not have a melting peak in the temperature range of 100°C to 420°C, the heat of melting is recorded as 0 J / g.
[0152] [Storage modulus (E') and loss modulus (E") of the adhesive layer]
[0153] A single-layer film obtained by the same steps as those for the single-layer film obtained in the evaluation of [Film Formability] is used as a measurement sample, and E' and E" are measured using a dynamic viscoelasticity measuring apparatus ("DM6100" manufactured by Hitachi High-Technologies Corporation). Specifically, the dynamic viscoelasticity of the sample is measured using the above-mentioned dynamic viscoelasticity measuring apparatus in an air atmosphere, and a graph is prepared by plotting E' and E" relative to the measurement temperature. From the graph, E' at temperatures of 360°C and 400°C and E" at a temperature of 400°C are read. The measurement conditions are shown below.
[0154] Width of sample: 9mm
[0155] Interval between sample holding tools (clamps): 20 mm
[0156] Measuring temperature range: 0℃~440℃
[0157] Heating rate: 3℃ / min
[0158] Deformation amplitude: 10μm
[0159] Measuring frequency: 5Hz
[0160] Minimum tension / compression force: 100mN
[0161] Tension / Compression Gain: 1.5
[0162] Initial force amplitude: 100mN
[0163] [Tertiary amine content]
[0164] Using measurement samples (mass: 0.5 mg) collected from each layer (specifically, the adhesive layer and the non-thermoplastic polyimide layer) of the multilayer polyimide film obtained in the examples and comparative examples described below, the tertiary amine content of each layer was measured using a thermal decomposition gas chromatography / mass spectrometry analyzer ("Py-GC / MS" manufactured by Agilent Technologies) at a heating temperature of 350°C.
[0165] [Dielectric loss tangent]
[0166] The single-layer film (adhesive layer), non-thermoplastic polyimide layer, and multilayer polyimide film (all layers) obtained in the Examples and Comparative Examples described below were used as test samples. The dielectric loss tangent was measured using a network analyzer (Keysight Technologies "N5224B") and a cavity resonator perturbation method dielectric constant measuring apparatus (EM LABO "CP531"). Specifically, the sample was left in an atmosphere of 23°C and 50% relative humidity for 24 hours. The dielectric loss tangent was then measured using the network analyzer and cavity resonator perturbation method dielectric constant measuring apparatus under the conditions of 23°C, 50% relative humidity, and a measurement frequency of 10 GHz. If the dielectric loss tangent of the multilayer polyimide film (all layers) was 0.0040 or less, it was evaluated as "the dielectric loss tangent was able to be reduced." On the other hand, if the dielectric loss tangent of the multilayer polyimide film (all layers) exceeded 0.0040, it was evaluated as "unable to reduce the dielectric loss tangent." It should be noted that for the non-thermoplastic polyimide layer, a single-layer film formed by removing the adhesive layers on both sides of the multilayer polyimide film obtained in the Examples and Comparative Examples described below with sandpaper (#600) was used as the measurement sample.
[0167] [Adhesion]
[0168] A 12 μm thick electrolytic copper foil ("CF-T49A-HD2" manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) was placed on both sides of a multilayer polyimide film (any of the multilayer polyimide films obtained in the Examples and Comparative Examples described below). Furthermore, a protective film ("Apical (registered trademark) 125NPI" manufactured by Kaneka Corporation, thickness: 125 μm) was placed on the outer surface of each electrolytic copper foil. In this state, the films were laminated using a hot roll laminator at a lamination temperature of 360°C, a lamination pressure of 314 N / cm (32 kgf / cm), and a lamination speed of 1.0 m / min to produce a flexible copper-clad laminate. The resulting flexible copper-clad laminate was analyzed in accordance with the "6.5 peel strength" of JIS C6471-1995. Specifically, one electrolytic copper foil of each flexible copper-clad laminate was peeled off at a peeling angle of 90°, a tensile speed of 100 mm / min, and a measurement width of 1 mm, and the load (unit: N / cm) was used as the adhesion strength. If the adhesion strength was 10 N / cm or more, it was evaluated as "excellent adhesion". On the other hand, if the adhesion strength was less than 10 N / cm, it was evaluated as "poor adhesion".
[0169] [Landfillability]
[0170] By etching, the copper foil of the flexible copper clad laminate obtained by the same steps as the flexible copper clad laminate obtained in the evaluation of [adhesion] is completely removed. Then, using an optical microscope, the surface of the exposed multilayer polyimide film is observed under the condition of 20 times the magnification. In addition, when the surface of the multilayer polyimide film is uniformly transferred with the rough surface of the copper foil, it is evaluated as "A (excellent in embedding)". On the other hand, when the surface of the multilayer polyimide film is not uniformly transferred with the rough surface of the copper foil, it is evaluated as "B (poor in embedding)".
[0171] If the adhesion strength is 10 N / cm or greater and the embedding property is rated A, it is evaluated as "adhesion properties to the metal layer are ensured." On the other hand, if the adhesion strength is less than 10 N / cm or the embedding property is rated B, it is evaluated as "adhesion properties to the metal layer are not ensured."
[0172] <Preparation of Polyamic Acid Solution>
[0173] The following describes the preparation methods of polyamic acid solutions P1 to P13. It should be noted that the preparation of polyamic acid solutions P1 to P13 was all carried out under a nitrogen atmosphere at a temperature of 20°C.
[0174] [Preparation of polyamic acid solution P1]
[0175] After adding 1477.48 kg of DMF, 27.28 kg of TPE-R and 57.24 kg of PDA into the reaction tank, 109.93 kg of BPDA was further added to stir the contents of the reaction tank. After visually confirming that BPDA had dissolved, 71.48 kg of ODPA was added to the reaction tank while stirring the contents of the reaction tank, and the contents of the reaction tank were stirred for 30 minutes. Then, while stirring the contents of the reaction tank, the pre-prepared PMDA solution (solvent: DMF, PMDA dissolution amount: 4.08 kg, PMDA concentration: 7.2 wt %) was added to the reaction tank at a rate that did not increase the viscosity of the reaction tank contents for a specified time. Furthermore, the addition of the PMDA solution and the stirring of the reaction tank contents were stopped at the moment when the viscosity of the reaction tank contents at a temperature of 23 ° C reached 2000 poise to obtain a polyamic acid solution P1.
[0176] For the polyimide obtained by the polyamic acid in the obtained polyamic acid solution P1, it is confirmed that it is non-thermoplastic using the method shown below. First, 40 weight parts of imidization accelerators including acetic anhydride / isoquinoline / DMF (weight ratio: acetic anhydride / isoquinoline / DMF=101 / 51 / 48) are added to 100 weight parts of polyamic acid solution P1 to prepare a non-thermoplastic polyimide layer forming solution. Then, the obtained non-thermoplastic polyimide layer is formed with a solution while being stirred with a mixer, while being extruded from the T die of a film-making device, and cast coated on an endless belt made of stainless steel to form a coating film. After the obtained coating film is dried at a temperature of 100°C for 380 seconds, the obtained gel film is peeled off from the endless belt and fixed to a tenter clamp. Then, after the gel film was heated at a temperature of 300 ℃ for 110 seconds, it was heated at a temperature of 380 ℃ for 97 seconds, so that the polyamic acid in the gel film was imidized to obtain a polyimide film with a thickness of 34 μm. The gained polyimide film was fixed to a metal fixed frame, heated for 2 minutes under the condition of 380 ℃ for a heating temperature, and the shape (film shape) of the polyimide film was maintained. Thus, the polyimide obtained by the polyamic acid in the polyamic acid solution P1 was a non-thermoplastic polyimide. It should be noted that, for the polyamic acid solutions P2 and P3 shown below for the preparation method, the polyimide film obtained by the same method as the method for forming a film using the above-mentioned polyamic acid solution P1 was fixed to a metal fixed frame, heated for 2 minutes under the condition of 380 ℃ for a heating temperature, and the shape (film shape) of the polyimide film was maintained. Thus, the polyimide obtained by the polyamic acid in the polyamic acid solutions P2 and P3 was all non-thermoplastic polyimide.
[0177] [Preparation of polyamic acid solution P2]
[0178] After adding 1404.80 kg of DMF, 27.87 kg of TPE-R and 58.48 kg of PDA into the reaction tank, 112.31 kg of BPDA was further added to stir the contents of the reaction tank. After visually confirming that BPDA had dissolved, 65.13 kg of ODPA was added to the reaction tank while stirring the contents of the reaction tank, and the contents of the reaction tank were stirred for 30 minutes. Then, while stirring the contents of the reaction tank, the pre-prepared PMDA solution (solvent: DMF, PMDA dissolution amount: 9.71 kg, PMDA concentration: 7.2 wt %) was added to the reaction tank at a rate that did not increase the viscosity of the reaction tank contents for a specified time. And when the viscosity of the reaction tank contents reached 2000 poise at a temperature of 23 ° C, the addition of PMDA solution and the stirring of the reaction tank contents were stopped to obtain a polyamic acid solution P2.
[0179] [Preparation of polyamic acid solution P3]
[0180] 1480.09 kg of DMF, 23.70 kg of 4,4'-diaminodiphenyl ether (hereinafter sometimes referred to as "ODA"), and 72.89 kg of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (hereinafter sometimes referred to as "BAPP") were added to a reaction vessel, and the contents were stirred. After visually confirming that the monomers had dissolved, 38.14 kg of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (hereinafter sometimes referred to as "BTDA") and 32.27 kg of PMDA were added to the reaction vessel while stirring the contents. The contents of the reaction vessel were stirred for 30 minutes. Next, 32.00 kg of PDA was added to the reaction vessel while stirring the contents of the reaction vessel, followed by 67.13 kg of PMDA, and the contents of the reaction vessel were stirred for 30 minutes. Next, while stirring the contents of the reaction tank, a previously prepared PMDA solution (solvent: DMF, PMDA dissolved in 3.87 kg, PMDA concentration: 7.2 wt%) was added to the reaction tank continuously for a predetermined time at a rate sufficient to prevent a sharp increase in the viscosity of the reaction tank contents. When the viscosity of the reaction tank contents reached 2000 poise at 23°C, the addition of the PMDA solution and stirring of the reaction tank contents were stopped, thereby obtaining a polyamic acid solution P3.
[0181] [Preparation of polyamic acid solution P4]
[0182] After adding 1507.46 kg of DMF, 98.25 kg of TPE-R, and 70.71 kg of BPDA to the reaction tank, the contents of the reaction tank were stirred for 30 minutes. Next, 15.73 kg of PMDA was added to the reaction tank while stirring the contents of the reaction tank, and the contents of the reaction tank were stirred for 30 minutes. Next, 30.61 kg of m-TB and 33.55 kg of PMDA were added to the reaction tank while stirring the contents of the reaction tank, and the contents of the reaction tank were stirred for 30 minutes. Next, while stirring the contents of the reaction tank, a pre-prepared PMDA solution (solvent: DMF, PMDA dissolved amount: 3.15 kg, PMDA concentration: 7.2 wt%) was added to the reaction tank continuously for a specified time at a rate that did not increase the viscosity of the reaction tank contents sharply. Furthermore, when the viscosity of the reaction tank contents reached 1000 poise at a temperature of 23°C, the addition of PMDA solution and the stirring of the reaction tank contents were stopped to obtain polyamic acid solution P4.
[0183] [Preparation of polyamic acid solution P5]
[0184] After adding 1508.32kg of DMF, 96.16kg of TPE-R and 89.97kg of BPDA into the reaction tank, the contents of the reaction tank were stirred for 30 minutes. Then, while stirring the contents of the reaction tank, 29.96kg of m-TB and 32.84kg of PMDA were added to the reaction tank, and the contents of the reaction tank were stirred for 30 minutes. Then, while stirring the contents of the reaction tank, a pre-prepared PMDA solution (solvent: DMF, PMDA dissolution amount: 3.08kg, PMDA concentration: 7.2 wt%) was added to the reaction tank at a rate that did not increase the viscosity of the reaction tank contents sharply for a specified time. Moreover, when the viscosity of the reaction tank contents reached 1000 poise at a temperature of 23°C, the addition of the PMDA solution and the stirring of the reaction tank contents were stopped to obtain a polyamic acid solution P5.
[0185] [Preparation of polyamic acid solution P6]
[0186] After adding 1506.86 kg of DMF, 99.70 kg of TPE-R, and 57.40 kg of BPDA to the reaction tank, the contents of the reaction tank were stirred for 30 minutes. Next, 26.60 kg of PMDA was added to the reaction tank while stirring the contents of the reaction tank, and the contents of the reaction tank were stirred for 30 minutes. Next, 31.06 kg of m-TB and 34.04 kg of PMDA were added to the reaction tank while stirring the contents of the reaction tank, and the contents of the reaction tank were stirred for 30 minutes. Next, while stirring the contents of the reaction tank, a pre-prepared PMDA solution (solvent: DMF, PMDA dissolution amount: 3.19 kg, PMDA concentration: 7.2 wt%) was added to the reaction tank continuously for a specified time at a rate that did not increase the viscosity of the reaction tank contents sharply. Furthermore, when the viscosity of the reaction tank contents reached 1000 poise at a temperature of 23°C, the addition of PMDA solution and the stirring of the reaction tank contents were stopped to obtain polyamic acid solution P6.
[0187] [Preparation of polyamic acid solution P7]
[0188] After adding 1541.34 kg of DMF, 91.60 kg of TPE-R and 131.86 kg of BPDA into the reaction tank, the contents of the reaction tank were stirred for 30 minutes. Then, after adding 25.69 kg of m-TB into the reaction tank while stirring the contents of the reaction tank, the contents of the reaction tank were stirred for 30 minutes. Then, while stirring the contents of the reaction tank, the pre-prepared m-TB solution (solvent: DMF, m-TB dissolution amount: 2.85 kg, m-TB concentration: 30 wt%) was added to the reaction tank at a rate that did not increase the viscosity of the reaction tank contents sharply for a predetermined time. Moreover, when the viscosity of the reaction tank contents reached 1000 poise at a temperature of 23 ° C, the addition of the m-TB solution and the stirring of the reaction tank contents were stopped to obtain a polyamic acid solution P7.
[0189] [Preparation of polyamic acid solution P8]
[0190] After adding 1541.39 kg of DMF, 97.45 kg of TPE-R and 130.93 kg of BPDA into the reaction tank, the contents of the reaction tank were stirred for 30 minutes. Then, while stirring the contents of the reaction tank, 20.78 kg of m-TB was added to the reaction tank, and the contents of the reaction tank were stirred for 30 minutes. Then, while stirring the contents of the reaction tank, a pre-prepared m-TB solution (solvent: DMF, amount of m-TB dissolved: 2.83 kg, concentration of m-TB: 30 wt%) was added to the reaction tank at a rate that did not increase the viscosity of the contents of the reaction tank sharply for a predetermined time. Moreover, when the viscosity of the contents of the reaction tank reached 1000 poise at a temperature of 23 ° C, the addition of the m-TB solution and the stirring of the contents of the reaction tank were stopped to obtain a polyamic acid solution P8.
[0191] [Preparation of polyamic acid solution P9]
[0192] After adding 1541.84kg of DMF, 96.99kg of TPE-R and 139.61kg of BPDA into the reaction tank, the reaction tank contents were stirred for 30 minutes. Then, after adding 13.85kg of PDA into the reaction tank while stirring the reaction tank contents, the reaction tank contents were stirred for 30 minutes. Then, while stirring the reaction tank contents, a pre-prepared PDA solution (solvent: DMF, PDA dissolution amount: 1.54kg, PDA concentration: 20% by weight) was added to the reaction tank at an addition rate that did not increase sharply in the viscosity of the reaction tank contents for a prescribed time. Furthermore, when the viscosity of the reaction tank contents reached 1000 poise at a temperature of 23°C, the addition of the PDA solution and the stirring of the reaction tank contents were stopped to obtain a polyamic acid solution P9.
[0193] [Preparation of polyamic acid solution P10]
[0194] After adding 1540.30 kg of DMF, 105.94 kg of TPE-R, and 113.05 kg of PMDA into the reaction tank, the contents of the reaction tank were stirred for 30 minutes. Next, while stirring the contents of the reaction tank, 29.71 kg of m-TB was added to the reaction tank, and the contents of the reaction tank were stirred for 30 minutes. Next, while stirring the contents of the reaction tank, a pre-prepared m-TB solution (solvent: DMF, m-TB dissolved amount: 3.30 kg, m-TB concentration: 30 wt%) was added to the reaction tank continuously for a predetermined time at a rate that did not increase the viscosity of the reaction tank contents sharply. Furthermore, when the viscosity of the reaction tank contents reached 1000 poise at a temperature of 23°C, the addition of the m-TB solution and the stirring of the reaction tank contents were stopped to obtain a polyamic acid solution P10.
[0195] [Preparation of polyamic acid solution P11]
[0196] After adding 1509.23 kg of DMF, 134.24 kg of TPE-R and 67.63 kg of BPDA into the reaction tank, the contents of the reaction tank were stirred for 30 minutes. Then, after adding 47.13 kg of PMDA into the reaction tank while stirring the contents of the reaction tank, the contents of the reaction tank were stirred for 30 minutes. Then, while stirring the contents of the reaction tank, the pre-prepared PMDA solution (solvent: DMF, PMDA dissolution amount: 3.01 kg, PMDA concentration: 7.2 wt %) was added to the reaction tank at an addition rate that did not increase the viscosity of the contents of the reaction tank for a specified time. Moreover, when the viscosity of the contents of the reaction tank reached 1000 poise at a temperature of 23 ° C, the addition of the PMDA solution and the stirring of the contents of the reaction tank were stopped to obtain a polyamic acid solution P11.
[0197] [Preparation of polyamic acid solution P12]
[0198] After adding 1514.99 kg of DMF, 160.67 kg of BAPP, and 23.03 kg of BPDA to the reaction tank, the reaction tank contents were stirred for 30 minutes. Next, while stirring the reaction tank contents, 65.73 kg of PMDA was added to the reaction tank, and the reaction tank contents were stirred for 30 minutes. Next, while stirring the reaction tank contents, a pre-prepared PMDA solution (solvent: DMF, PMDA dissolution amount: 2.56 kg, PMDA concentration: 7.2 wt %) was added to the reaction tank at a rate that did not increase the viscosity of the reaction tank contents sharply for a specified time. Furthermore, when the viscosity of the reaction tank contents reached 1000 poise at a temperature of 23°C, the addition of the PMDA solution and the stirring of the reaction tank contents were stopped to obtain a polyamic acid solution P12.
[0199] [Preparation of polyamic acid solution P13]
[0200] After adding 1510.01kg of DMF, 124.96kg of TPE-R and 92.78kg of BPDA into the reaction tank, the reaction tank contents were stirred for 30 minutes. Then, while stirring the reaction tank contents, 4.78kg of m-TB and 26.53kg of PMDA were added to the reaction tank, and the reaction tank contents were stirred for 30 minutes. Then, while stirring the reaction tank contents, a pre-prepared PMDA solution (solvent: DMF, PMDA dissolution amount: 2.95kg, PMDA concentration: 7.2 wt%) was added to the reaction tank at an addition rate that did not increase the viscosity of the reaction tank contents sharply for a specified time. Moreover, when the viscosity of the reaction tank contents reached 1000 poise at a temperature of 23°C, the addition of the PMDA solution and the stirring of the reaction tank contents were stopped to obtain a polyamic acid solution P13.
[0201] Table 1 shows the materials used in each of the polyamic acid solutions P1 to P13 and their proportions. The molar fraction of each residue in the polyamic acid contained in each of the polyamic acid solutions P1 to P13 is consistent with the molar fraction of each monomer (diamine and tetracarboxylic dianhydride) used. In addition, Table 2 shows the results obtained by measuring and evaluating the monolayer films obtained using the above method using the polyamic acid solutions P4 to P13 respectively. It should be noted that in Table 1, "-" means that the component is not used. In Table 1, the numerical value in the "acid dianhydride" column is the content rate of each acid dianhydride relative to the total amount of the acid dianhydride used (unit: mole %). In Table 1, the numerical value in the "diamine" column is the content rate of each diamine relative to the total amount of the diamine used (unit: mole %). In addition, in Table 2, "-" means that no measurement was performed.
[0202] [Table 1]
[0203]
[0204] [Table 2]
[0205]
[0206] <Production of Multilayer Polyimide Film>
[0207] Hereinafter, the method for producing the multilayer polyimide films of Examples 1 to 5 and Comparative Examples 1 to 5 will be described.
[0208] [Example 1]
[0209] As an imidization accelerator, a mixture of 144 kg of DMF, 153 kg of isoquinoline, and 303 kg of acetic anhydride was prepared. This imidization accelerator was added to the polyamic acid solution P1, and the mixture was stirred using a mixer to obtain a non-thermoplastic polyimide layer forming solution. The amount of the imidization accelerator added was 40 parts by weight relative to 100 parts by weight of the polyamic acid solution P1. In addition, as an adhesive layer forming solution, a polyamic acid solution P4 was prepared.
[0210] Next, using an extrusion molding machine with a three-layer extrusion molding die, a non-thermoplastic polyimide layer forming solution and an adhesive layer forming solution are applied to a stainless steel endless belt as a support by a coextrusion-cast coating method. Specifically, the non-thermoplastic polyimide layer forming solution is first supplied to the central layer of the extrusion molding die, and the adhesive layer forming solution is supplied to the two layers (on both sides) adjacent to the central layer of the extrusion molding die. In addition, the opening width of the lip opening of the extrusion molding die (the length of the short side direction of the lip opening) is adjusted to 1.3 mm. Next, by a coextrusion-cast coating method, a non-thermoplastic polyimide layer forming solution and an adhesive layer forming solution are extruded from the lip opening of the extrusion molding die to form a coating film (a coating film consisting of three layers of adhesive layer forming solution / non-thermoplastic polyimide layer forming solution / adhesive layer forming solution) on the stainless steel endless belt. The resulting coating film was dried on a stainless steel endless belt at 100°C for 380 seconds to obtain a gel film. After peeling the gel film from the stainless steel endless belt, both ends in the longitudinal direction were pinned and heated at 300°C for 110 seconds, then at 380°C (maximum temperature) for 97 seconds to imidize the polyamic acid in the non-thermoplastic polyimide layer-forming solution and the polyamic acid in the adhesive layer-forming solution, thereby obtaining the multilayer polyimide film of Example 1. The multilayer polyimide film of Example 1 had a three-layer structure of adhesive layer / non-thermoplastic polyimide layer / adhesive layer, with the thickness of each layer being adhesive layer / non-thermoplastic polyimide layer / adhesive layer = 8 μm / 34 μm / 8 μm.
[0211] Furthermore, for the multilayer polyimide film of Example 1, the tertiary amine (isoquinoline) content of each layer was measured using the above-described method using measurement samples (mass: 0.5 mg) taken from each of the adhesive layer and the non-thermoplastic polyimide layer. The results showed that isoquinoline was detected at a content of 1 ppm by mass or greater in both the adhesive layer and the non-thermoplastic polyimide layer. It should be noted that the tertiary amine (isoquinoline) content of each layer in Examples 2 to 5 and Comparative Examples 1 to 5 described below was also measured using the same method as in Example 1. The results showed that isoquinoline was detected at a content of 1 ppm by mass or greater in both the adhesive layer and the non-thermoplastic polyimide layer.
[0212] [Examples 2 to 5 and Comparative Examples 1 to 5]
[0213] Multilayer polyimide films of Examples 2 to 5 and Comparative Examples 1 to 5 were obtained by the same method as in Example 1, except that the type of the polyamic acid solution used to prepare the solution for forming the non-thermoplastic polyimide layer and the type of the polyamic acid solution used as the solution for forming the adhesive layer were set as shown in Table 3 described below.
[0214] <Attempt to Prepare Multilayer Polyimide Film>
[0215] [Comparative Example 6]
[0216] An attempt was made to obtain a multilayer polyimide film by the same method as in Example 1 except that polyamic acid solution P10 was used instead of polyamic acid solution P4 as the adhesive layer forming solution. However, the film cracked and a good film could not be obtained.
[0217] [Comparative Example 7]
[0218] An attempt was made to obtain a multilayer polyimide film by the same method as in Example 1 except that polyamic acid solution P11 was used instead of polyamic acid solution P4 as the adhesive layer forming solution. However, the film cracked and a good film could not be obtained.
[0219] [Comparative Example 8]
[0220] Do not add imidization accelerator to polyamic acid solution P1, polyamic acid solution P1 is used as non-thermoplastic polyimide layer forming solution, in addition, utilize the method identical with above-mentioned Example 1, attempt to obtain multilayer polyimide film, but film produces wrinkles, and good film cannot be obtained.Use the determination sample (quality: 0.5mg) taken from the position that does not produce wrinkles of film surface (adhesive layer), utilize the above-mentioned method to measure the containing rate of tertiary amine, as a result, no tertiary amine is detected. In other words, in comparative example 8, the containing rate of tertiary amine in adhesive layer is less than detection limit (1 mass ppm).In addition, use the determination sample (quality: 8mg) taken from the position that does not produce wrinkles of film surface (adhesive layer), utilize the above-mentioned method to measure melting temperature and melting heat, as a result, melting temperature and melting heat are respectively 333 ℃ and 2.3J / g.
[0221] <Preparation of Polyimide Film of Reference Example>
[0222] As a reference example, a single-layer polyimide film was prepared. In the preparation of the polyimide film of the reference example, no imidization accelerator was added to the polyamic acid solution P4, and the polyamic acid solution P4 was used as a coating liquid. First, using Commacoater (registered trademark), the polyamic acid solution P4 was coated on one side of an electrolytic copper foil ("CF-T49A-HD2" manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) with a thickness of 12 μm to form a coating film. Then, a gel film was obtained by drying the coating film at a temperature of 130°C for 120 seconds. After heating the obtained gel film at a temperature of 120°C for 5 minutes, the temperature was increased to 350°C at a heating rate of 5°C / min, and then heated at a temperature of 350°C for 30 minutes to imidize the polyamic acid in the coating film to obtain a polyimide film with a thickness of 12 μm. The tertiary amine content was measured using the above method using a measurement sample (mass: 0.5 mg) taken from the polyimide film of the Reference Example. No tertiary amine was detected. In other words, the tertiary amine content in the polyimide film of the Reference Example was below the detection limit (1 mass ppm). Furthermore, the melting temperature and heat of fusion were measured using the above method using a measurement sample (mass: 8 mg) taken from the polyimide film of the Reference Example. The results were 333°C and 2.3 J / g, respectively.
[0223] <Evaluation Results>
[0224] For Examples 1 to 5 and Comparative Examples 1 to 5, the type of polyamic acid solution used to prepare a solution for forming a non-thermoplastic polyimide layer, the type of polyamic acid solution used as a solution for forming an adhesive layer, the melting temperature of the adhesive layer, and the melting heat of the adhesive layer are shown in Table 3. In addition, for Examples 1 to 5 and Comparative Examples 1 to 5, the adhesion strength, embedding property, and dielectric loss tangent are shown in Table 4. It should be noted that in Table 3, "non-thermoplastic solution" refers to a polyamic acid solution used to prepare a solution for forming a non-thermoplastic polyimide layer. In Table 3, "adhesive solution" refers to a polyamic acid solution used as a solution for forming an adhesive layer. In Table 3, "no peak" means that there is no melting peak in the temperature range of 100°C to 420°C.
[0225] [Table 3]
[0226]
[0227] [Table 4]
[0228]
[0229] The polyamic acid contained in the adhesive layer forming solution used in the preparation of the multilayer polyimide films of Examples 1 to 5 has a PMDA residue, a BPDA residue, a TPE-R residue and an m-TB residue. The polyamic acid contained in the non-thermoplastic polyimide layer forming solution used in the preparation of the multilayer polyimide films of Examples 1 to 5 has one or more tetracarboxylic dianhydride residues selected from the group consisting of BPDA residues and ODPA residues, and one or more diamine residues selected from the group consisting of PDA residues and TPE-R residues. The dielectric loss tangent of the non-thermoplastic polyimide layer possessed by the multilayer polyimide films of Examples 1 to 5 is less than 0.0030. The adhesive layer possessed by the multilayer polyimide films of Examples 1 to 5 does not have a melting peak in the temperature range of 100°C to 420°C.
[0230] In the multilayer polyimide films of Examples 1 to 5, the adhesion strength was 10 N / cm or greater. Therefore, the multilayer polyimide films of Examples 1 to 5 had excellent adhesion. In the multilayer polyimide films of Examples 1 to 5, the embedding performance was evaluated as A. Therefore, the multilayer polyimide films of Examples 1 to 5 had excellent embedding performance. In the multilayer polyimide films of Examples 1 to 5, the dielectric loss tangent of all layers was 0.0040 or less. Therefore, the multilayer polyimide films of Examples 1 to 5 were able to reduce the dielectric loss tangent.
[0231] The polyamic acid contained in the adhesive layer forming solution used in the preparation of the multilayer polyimide films of Comparative Examples 1 to 3 does not have a PMDA residue. The polyamic acid contained in the adhesive layer forming solution used in the preparation of the multilayer polyimide film of Comparative Example 3 does not have an m-TB residue. The polyamic acid contained in the adhesive layer forming solution used in the preparation of the multilayer polyimide film of Comparative Example 4 does not have a TPE-R residue and an m-TB residue. The polyamic acid contained in the non-thermoplastic polyimide layer forming solution used in the preparation of the multilayer polyimide film of Comparative Example 5 does not have one or more tetracarboxylic dianhydride residues selected from the group consisting of BPDA residues and ODPA residues. The dielectric loss tangent of the non-thermoplastic polyimide layer possessed by the multilayer polyimide film of Comparative Example 5 exceeds 0.0030. The heat of fusion of the melting peak of the adhesive layer possessed by the multilayer polyimide films of Comparative Examples 1 to 4 exceeds 1.0 J / g.
[0232] The multilayer polyimide films of Comparative Examples 1 to 4 had an adhesion strength of less than 10 N / cm. Therefore, the multilayer polyimide films of Comparative Examples 1 to 4 did not have excellent adhesion. The multilayer polyimide films of Comparative Examples 1 to 3 had a fill rating of B. Therefore, the multilayer polyimide films of Comparative Examples 1 to 3 did not have excellent fill properties. In the multilayer polyimide film of Comparative Example 5, the dielectric loss tangent of all layers exceeded 0.0040. Therefore, the multilayer polyimide film of Comparative Example 5 was unable to reduce the dielectric loss tangent.
[0233] The above results indicate that the present invention can provide a multilayer polyimide film and a method for producing the film, which can ensure adhesion to a metal layer and reduce dielectric loss tangent.
[0234] Description of Reference Numerals
[0235] 10: Multilayer polyimide film
[0236] 11: Non-thermoplastic polyimide layer
[0237] 12: Adhesive layer
[0238] 13: Metal layer
[0239] 20: Metal foil laminate
Claims
1. A multilayer polyimide film comprising a non-thermoplastic polyimide layer and an adhesive layer disposed on at least one side of the non-thermoplastic polyimide layer, wherein the adhesive layer comprises polyimide, The dielectric loss tangent of the non-thermoplastic polyimide layer is less than 0.0030 at a frequency of 10 GHz, a temperature of 23° C., and a relative humidity of 50%. The adhesive layer has no melting peak in the temperature range of 100° C. to 420° C. or less, or the melting heat of the melting peak is 1.0 J / g or less, The polyimide contained in the adhesive layer has one or more tetracarboxylic dianhydride residues selected from the group consisting of pyromellitic dianhydride residues and 3,3',4,4'-biphenyltetracarboxylic dianhydride residues, and one or more diamine residues selected from the group consisting of 1,3-bis(4-aminophenoxy)benzene residues and 4,4'-diamino-2,2'-dimethylbiphenyl residues. The non-thermoplastic polyimide contained in the non-thermoplastic polyimide layer has a p-phenylenediamine residue and a 1,3-bis(4-aminophenoxy)benzene residue as diamine residues, The content of the p-phenylenediamine residue is 60 mol% or more and 95 mol% or less relative to all diamine residues constituting the non-thermoplastic polyimide, The content of the 1,3-bis(4-aminophenoxy)benzene residue is 5 mol % or more and 40 mol % or less relative to all diamine residues constituting the non-thermoplastic polyimide.
2. The multilayer polyimide film according to claim 1, wherein The adhesive layer is disposed on both sides of the non-thermoplastic polyimide layer.
3. The multilayer polyimide film according to claim 1 or 2, wherein: The adhesive layer contains a tertiary amine at a content of 1 mass ppm or more.
4. The multilayer polyimide film according to claim 1 or 2, wherein: The non-thermoplastic polyimide layer contains a tertiary amine at a content of 1 mass ppm or more.
5. The multilayer polyimide film according to claim 1 or 2, wherein: The non-thermoplastic polyimide contained in the non-thermoplastic polyimide layer has one or more tetracarboxylic dianhydride residues selected from the group consisting of 3,3′,4,4′-biphenyltetracarboxylic dianhydride residues and 4,4′-oxydiphthalic anhydride residues.
6. The multilayer polyimide film according to claim 5, wherein: The polyimide contained in the adhesive layer does not have a p-phenylenediamine residue.
7. The multilayer polyimide film according to claim 5, wherein: The content of the 4,4′-oxydiphthalic anhydride residue is 10 mol % or more and 50 mol % or less relative to all tetracarboxylic dianhydride residues constituting the non-thermoplastic polyimide.
8. The multilayer polyimide film according to claim 1 or 2, wherein: The adhesive layer does not have a melting peak within a temperature range of 100° C. to 420° C. 9 . A metal foil-clad laminate comprising the multilayer polyimide film according to claim 1 , and a metal layer disposed on a main surface of at least one of the adhesive layers of the multilayer polyimide film.
10. A method for producing a multilayer polyimide film, the multilayer polyimide film comprising a non-thermoplastic polyimide layer and an adhesive layer disposed on at least one surface of the non-thermoplastic polyimide layer, the adhesive layer comprising polyimide, the method comprising the following steps: a coating step of coating a non-thermoplastic polyimide layer-forming solution containing polyamic acid, acetic anhydride and tertiary amine and an adhesive layer-forming solution containing polyamic acid on a support by a coextrusion-casting coating method; a gel thin film forming step of drying the coating film obtained in the coating step to form a self-supporting gel thin film; and an imidization step of heating the gel film obtained in the gel film forming step at a maximum temperature of 360° C. or higher to imidize the polyamic acid in the non-thermoplastic polyimide layer forming solution and the polyamic acid in the adhesive layer forming solution, In the coating step, the polyamic acid contained in the adhesive layer forming solution has a pyromellitic dianhydride residue, a 3,3',4,4'-biphenyltetracarboxylic dianhydride residue, a 1,3-bis(4-aminophenoxy)benzene residue, and a 4,4'-diamino-2,2'-dimethylbiphenyl residue, In the coating step, the polyamic acid contained in the non-thermoplastic polyimide layer-forming solution has at least one selected from the group consisting of 3,3',4,4'-biphenyltetracarboxylic dianhydride residues and 4,4'-oxydiphthalic anhydride residues as tetracarboxylic dianhydride residues, and has a p-phenylenediamine residue and a 1,3-bis(4-aminophenoxy)benzene residue as diamine residues, The content of the p-phenylenediamine residue is 60 mol % or more and 95 mol % or less relative to all diamine residues constituting the polyamic acid contained in the solution for forming the non-thermoplastic polyimide layer, The content of the 1,3-bis(4-aminophenoxy)benzene residue is 5 mol % or more and 40 mol % or less relative to all diamine residues constituting the polyamic acid contained in the solution for forming the non-thermoplastic polyimide layer, The dielectric loss tangent of the non-thermoplastic polyimide layer is less than 0.0030 at a frequency of 10 GHz, a temperature of 23° C., and a relative humidity of 50%. The adhesive layer has no melting peak in a temperature range of 100° C. to 420° C., or has a melting heat of 1.0 J / g or less.
11. The method for producing a multilayer polyimide film according to claim 10, wherein: In the coating step, the polyamic acid contained in the adhesive layer forming solution does not have a p-phenylenediamine residue.
12. The method for producing a multilayer polyimide film according to claim 10 or 11, wherein: In the imidization step, a heating time of the gel film at the maximum temperature is 10 seconds to 300 seconds.
13. The method for producing a multilayer polyimide film according to claim 10, wherein: The adhesive layer does not have a melting peak within a temperature range of 100° C. to 420° C.
14. The method for producing a multilayer polyimide film according to claim 10 or 11, wherein: The content of the 4,4′-oxydiphthalic anhydride residue is 10 mol % or more and 50 mol % or less relative to all tetracarboxylic dianhydride residues constituting the polyamic acid contained in the solution for forming the non-thermoplastic polyimide layer.
Citation Information
Patent Citations
Polyimide film, copper-clad laminate, and circuit substrate
WO2018061727A1
Polyimide film, copper-clad laminate, and circuit substrate
CN109789689A
Multilayer polyimide film
JP2018145303A